Mapping Social Entrepreneurship Concepts through Bibliometric Analysis - Dunggio, Titin; Uhai, Sabalius; Evly, Festus; Limpo, Lita; Sampe, Ferdinandus (The Es Economics and Entrepreneurship, 2024)
Social entrepreneurship has emerged as a significant force in addressing societal challenges through entrepreneurial approaches aimed at creating sustainable solutions. Despite its growing interest, the conceptual framework of social entrepreneurship remains complex and multifaceted, with diverse interpretations and applications. This paper conducts a systematic bibliometric analysis to map the landscape of social entrepreneurship concepts, elucidating key themes, trends, and intellectual connections within the literature. Through advanced bibliometric techniques, including network analysis and thematic clustering, the study identifies seminal works, influential authors, and emerging research topics in the field. The analysis reveals shifts in research focus over time, from foundational concepts to the integration of technology and crowdsourcing methods. Furthermore, potential emerging research areas are identified, offering opportunities for future inquiry. The findings contribute to a nuanced understanding of the conceptual landscape and intellectual structure of social entrepreneurship research, informing scholarly inquiry, policy formulation, and practical interventions in the field.